2020
DOI: 10.3390/nu12030649
|View full text |Cite
|
Sign up to set email alerts
|

The Modelled Population Obesity-Related Health Benefits of Reducing Consumption of Discretionary Foods in Australia

Abstract: Over one third of Australians’ daily energy intake is from discretionary foods and drinks. While many health promotion efforts seek to limit discretionary food intake, the population health impact of reductions in the consumption of different types of discretionary foods (e.g., sugar-sweetened beverages (SSBs), confectionery, sweet biscuits) has not been quantified. This study estimated the potential reductions in body weight, obesity-related disease incidence, and healthcare cost savings associated with consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The decrease in body weight was also positively correlated with the decrease in consumption of the so-called discretionary foods: confectionery, salty snacks, commercial pastry, fast food, and sugar-sweetened beverages. Such an effect is a confirmed phenomenon, that reducing the consumption of those types of foods and replacing them, even partially, with healthy products leads to weight loss in people of all ages [50]. Our results prove that weight loss during the lockdown period was achieved by changes in eating behavior toward a healthier diet.…”
Section: Discussionsupporting
confidence: 69%
“…The decrease in body weight was also positively correlated with the decrease in consumption of the so-called discretionary foods: confectionery, salty snacks, commercial pastry, fast food, and sugar-sweetened beverages. Such an effect is a confirmed phenomenon, that reducing the consumption of those types of foods and replacing them, even partially, with healthy products leads to weight loss in people of all ages [50]. Our results prove that weight loss during the lockdown period was achieved by changes in eating behavior toward a healthier diet.…”
Section: Discussionsupporting
confidence: 69%
“…Different fresh meats and alternatives were separately studied as meats have been reported to be important sources of dietary GHG emissions [ 33 , 34 , 35 , 36 , 37 ]. Different discretionary choices were also separately examined because they are widely overconsumed by Australians and are a major public health nutrition concern [ 38 , 39 , 40 ]. Discretionary choices are energy-dense and nutrient-poor foods and beverages high in saturated fat, added sugars and salt, and alcohol [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…To demonstrate the clinical practice implications of minor dietary adjustments, Lal et al . ( 130 ) modelled the impact of a small reduction in energy‐dense, nutrient‐poor food consumption in Australia. Substituting or replacing specific EDNP foods resulted in an estimated 6–57 kJ day –1 per food serve reduction in total energy intake for children aged 7–18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Substituting or replacing specific EDNP foods resulted in an estimated 6–57 kJ day –1 per food serve reduction in total energy intake for children aged 7–18 years. Importantly, further modelling identified that these change were associated with significant population level health improvements and substantial healthcare cost savings ( 130 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation